2019
DOI: 10.1038/s41598-019-42584-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile in patients with Gaucher disease indicates activation of inflammatory processes

Abstract: Gaucher disease (GD) is a rare inherited metabolic disease caused by pathogenic variants in the GBA1 gene. So far, the pathomechanism of GD was investigated mainly in animal models. In order to delineate the molecular changes in GD cells we analysed gene expression profile in cultured skin fibroblasts from GD patients, control individuals and, additionally, patients with Niemann-Pick type C disease (NPC). We used expression microarrays with subsequent validation by qRT-PCR method. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
(48 reference statements)
3
12
0
Order By: Relevance
“…In agreement with a recent publication by Lugowska et al using GD fibroblasts [ 18 ], we found that GD macrophages exhibited significant up-regulation of a number of other immune response genes, including IFIT1 , IFIT2 , MX1 , OAS2 , and LY6E [ 18 ]. Future experiments will explore whether any of these genes could be used as potential new GD biomarkers.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with a recent publication by Lugowska et al using GD fibroblasts [ 18 ], we found that GD macrophages exhibited significant up-regulation of a number of other immune response genes, including IFIT1 , IFIT2 , MX1 , OAS2 , and LY6E [ 18 ]. Future experiments will explore whether any of these genes could be used as potential new GD biomarkers.…”
Section: Resultssupporting
confidence: 93%
“…GD patients are primed for oxidative response complications because they are known to have a severe redox imbalance partially caused by alterations in catalase activity [ 44 ]. While plasma from GD patients has elevated catalase enzymatic activity, GD RBCs have significantly lower catalase activity [ 18 , 45 ]. We found that unstimulated GD macrophages express significantly lower levels of CAT , the gene that encodes for catalase, than unstimulated control macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SPC may also be implicated in chronic vascular disease with involvement in processes such as proliferation and migration of vascular smooth muscle cells by acting as a pro-inflammatory mediator by activating p38 mitogen-activated protein kinases [ 36 ]. This is consistent with inflammation being involved in the pathogenesis of GD [ 37 ]. However, SPC (similar to N-palmitoyl-O-phosphocholineserine) is not specific to Gaucher disease.…”
Section: Resultssupporting
confidence: 87%
“…The human ISLR protein, a member of the Ig superfamily, contains a leucine-rich repeat (LRR) with conserved flanking sequences and a C2type immunoglobulin (Ig)-like domain (Nagasawa et al, 1997). The ISLR protein has been reported to be involved in some biological events, such as cell replicative senescence of human dermal fibroblasts (Yoon et al, 2004), embryo development (Homma et al, 2009), and Gaucher disease (Lugowska et al, 2019). However, no study has mainly investigated the potential functional relationship between the ISLR gene and cancer events thus far.…”
Section: Introductionmentioning
confidence: 99%